2021
DOI: 10.1007/s40495-021-00262-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pharmacologic Treatment of COVID-19 Pandemic in Iraq

Abstract: The impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, or COVID-19) has been detrimental to human health, economy, and wellbeing. Little information is known on the epidemiology and outcome of the disease in a localized community within Iraq. We carried out an audit of confirmed cases of COVID-19 in the Kirkuk General Hospital. Data from the 20th of June to the 31st of July, 2020, were collected and analyzed. Suspected COVID-19 cases were confirmed by real-time polymerase chain reaction (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
(28 reference statements)
2
14
0
Order By: Relevance
“…Finally, the current study shows that HCQ was a highly significant improvement in oxidative stress parameter (MDA), and TG concentrations in the serum patients with RA compared with RA patients on conventional therapy and control and was a highly significant improvement in MDA and TG levels in comparison with conventional therapy. It is worthy to mention that hydroxychloroquine is used in COVID-19 with an obscure mechanism of action [45][46][47][48][49], either alone or with zinc as a cofactor for potential therapy [50]. While the proposed mechanism also involved reduced oxidative and pro-inflammatory damage, nonetheless, these data need further confirmation at a molecular level to confirm the therapeutic activities.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the current study shows that HCQ was a highly significant improvement in oxidative stress parameter (MDA), and TG concentrations in the serum patients with RA compared with RA patients on conventional therapy and control and was a highly significant improvement in MDA and TG levels in comparison with conventional therapy. It is worthy to mention that hydroxychloroquine is used in COVID-19 with an obscure mechanism of action [45][46][47][48][49], either alone or with zinc as a cofactor for potential therapy [50]. While the proposed mechanism also involved reduced oxidative and pro-inflammatory damage, nonetheless, these data need further confirmation at a molecular level to confirm the therapeutic activities.…”
Section: Resultsmentioning
confidence: 99%
“…The azithromycin dosage used in the study was significantly lower than the hydroxychloroquine dosage used in the research, despite the fact that the hydroxychloroquine was obtained from our hospital. For the therapeutic remedies of severe COVID-19 infection in individuals who are apparently free from cardiovascular risk factors, the combination of hydroxychloroquine and azithromycin was investigated (5). In laboratory animals, hydroxychloroquine, either alone or combined with azithromycin, was shown to reduce COVID-19 mortality (18).…”
Section: Discussionmentioning
confidence: 99%
“…When 1561 COVID-19 patients were brought to the hospital for treatment, researchers from RECOVERY found that large dosages of hydroxychloroquine didn't have any impact on 28-day mortality, but they did have detrimental consequences on their health (Increased length of stay in the hospital, progression to invasive mechanical ventilation, and eventual death) (9). Furthermore, it was shown that hydroxychloroquine was unsuccessful in COVID-19 patients who were admitted to the hospital, independent of the dosage administered (5). Patients with moderate to severe COVID-19 related dyspnea who received hydroxychloroquine and azithromycin did not experience a reduction in mortality, a reduction in the need for invasive oxygen treatment, a reduction in the rate of ICU transfers, or a reduction in the length of hospital stay, according to the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…or patients' history of previous medications should be considered from the point of view of polypharmacy and its impact on geriatric patients [55][56][57][58], moreover, some drugs are tonic multivitamins [59][60][61]or zinc [62][63][64]which cud be used as add-on therapy for patients with other diseases and greatly impact the disease outcome or pathogenicity.…”
Section: Polypharmacy and Lifestyle: Role Of Ageingmentioning
confidence: 99%